Improving Science Learning Outcomes on Energy and its Changes through Audio Visual Media Assisted Problem-Based Learning (PBL) Model for Fourth-Grade Elementary School Students - Putri Angriani; Meylan saleh; Gamar Abdullah; Rifda Mardian Arif; Vicka muniati Arifin (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This research was motivated by the low learning outcomes of fourth-grade students at SDN 7 Dungaliyo in Natural Sciences (IPA), specifically on Energy and Its Changes material. This issue was driven by the abstract nature of the topic and a teacher-centered learning environment that lacked varied learning media. This study aimed to improve the learning outcomes of fourth-grade students at SDN 7 Dungaliyo through the application of the Problem-Based Learning (PBL) model assisted by audio-visual media. The research design employed a Classroom Action Research (CAR) based on the Hopkins model, conducted in two cycles. Each cycle encompassed four major phases: planning, acting, observing, and reflecting. The subjects of this research were all 18 fourth-grade students at SDN 7 Dungaliyo, Gorontalo Regency, during the 2025/2026 academic year, consisting of 12 male and 6 female students. Data collection techniques included observation of teacher and student activities, multiple-choice written evaluation tests, and classroom documentation. The gathered data were analyzed descriptively using percentage techniques. The results demonstrated a significant improvement in student learning outcomes across the cycles. In the pre-action baseline condition, the classical mastery reached only 34% (6 students) meeting the Minimum Mastery Criteria (KKM 70). Following the implementation of Cycle I, the student learning mastery percentage increased slightly to 39% (7 students), which still fell short of the targeted classical success indicator. Reflective improvements were made in Cycle II by enhancing the interactivity of audio-visual media and group engagement. The evaluation in Cycle II revealed a substantial surge in classical mastery, reaching 83% (15 students) who successfully met the Learning Objectives Achievement Criteria (KKTP). The mastery growth from Cycle I to Cycle II was recorded at 44%. Based on these findings, it can be concluded that the application of the Problem-Based Learning (PBL) model assisted by audio-visual media is highly effective in improving science learning outcomes on Energy and Its Changes for fourth-grade students at SDN 7 Dungaliyo, Gorontalo Regency.